Device-Associated Nosocomial Infection Rates and Distribution of Antimicrobial Resistance in a Medical-Surgical Intensive Care Unit in Turkey - TİGEN, ELİF (NATL INST INFECTIOUS DISEASES, 2014)
The aim of this study was to explore the rate of device-associated nosocomial infections (DANIs) and the distributions of causative agents and patterns of antibiotic resistance in the medical-surgical intensive care unit (ICU) over a 3-year period and to compare these rates with those reported by National Nosocomial Infections Surveillance System and International Nosocomial Infection Control Consortium. A total of 1,798 patients were hospitalized in our ICU for 13,942 days, of which 309 patients had DANIs, indicating an overall infection rate of 22.1 per 1,000 ICU-days. The central line-associated bloodstream infection rate was 6.4 per 1,000 catheter-days, whereas the ventilator-associated pneumonia rate was 14.3 per 1,000 ventilator-days and the catheter-associated urinary tract infection rate was 4.3 per 1,000 catheter-days. Overall, 87.4% of all Staphylococcus aureus DANIs were caused by methicillin-resistant strains. With respect to Pseudomonas aeruginosa, 30.9% of the strains were resistant to ciprofloxacin, 23.3% to amikacin, 43.1% to ceftazidime, 19.1% to piperacillin-tazobactam, and 34.7% to imipenem. Furthermore, 1.9% of the Enterococcus spp. were resistant to vancomycin, and 51.1% of Enterobacteriaceae were resistant to ceftriaxone. DANI rates decreased over the 3-year study period, which was likely in response to the infection control measures implemented in our ICU.
Keywords: MORTALITY